Redescription of Ichthyofilaria argentinensis Incorvaia, 1999 (Nematoda: Philometridae) parasite of Merluccius hubbsi (Pisces: Merlucciidae) from Argentina - Tim, J T; Navone, G T; Sardella, N H (Folia parasitologica, 2001)
Ichthyofilaria argentinensis Incorvaia, 1999 (Nematoda: Philometridae) is redescribed from type specimens and from parasites collected from the swim bladder of Argentine hakes Merluccius hubbsi Marini, 1933 caught at the Gulf of San Jorge (46 degrees 30'S, 66 degrees 30'W), Argentine Sea, in July, 1998. Sixteen out of 80 hakes (20%) were found to be parasitised by gravid females of this philometrid. After revision of both these nematodes and type material, the following differences from the original description of the species were observed: (a) cuticle with fine transverse striations, instead of smooth cuticle; (b) presence of cephalic papillae and a pair of amphids; (c) absence of swellings in the oesophagus; (d) oesophageal gland appendix very large and lobulate rather than small and vermiform, and (d) presence of vulva and vagina. The morphological features given in the redescription allow the confirmation of the identity of I. argentinensis as a valid species and to distinguish it from other members of the genus.
Keywords: ryby; hlístice; vzdušné vaky; histocytochemie; Fishes; Histocytochemistry; Animals; Female; ženské pohlaví; Nematoda; Argentina; zvířata; Air Sacs